Spatiotemporal Variation of Frost within Growing Periods - Mokhele Edmond Moeletsi; Mphethe Isaac Tongwane (Advances in Meteorology)
Frost is one of the devastating agroclimatological hazards affecting crop production in the Free State Province of South Africa. In this study, frost (0°C threshold) probabilities within different growing periods starting from the first dekad of October to the third dekad of February for a 100-day, 120-day, and 140-day crop were determined. The data used in the investigation was daily minimum temperature obtained from 55 weather stations located in and around the Free State Province with data from 1950 to 2010. The results show high spatial and temporal variability of frost within the different growing periods. The western, central, northern, and northwestern parts of the province have the longest planting window for all the growing lengths from mid-October to mid-January. The eastern, northeastern, southern, and southeastern parts of Free State have the highest frost risk with shortened planting window mostly from the first dekad of November to the second dekad of December. Thus, careful consideration of frost incidences is important for successful crop production in this area.